Semantic processing event‐related potential features in patients with schizophrenia and bipolar disorder. Issue 2 (1st December 2019) - Wang, Kui; Zhao, Yan‐li; Tan, Shu‐ping; Zhang, Jin‐guo; Li, Dong; Chen, Jing‐xu; Zhang, Li‐gang; Yu, Xin‐yang; Zhao, Dan; Cheung, Eric F. C.; Turetsky, Bruce I.; Gur, Ruben C.; et al.
Abstract: Impairment in semantic association has been reported in bipolar disorder (BD) and schizophrenia (SZ) patients and could underlie abnormal speech patterns in both disorders. In this study, we compared the electrophysiological semantic processing features in patients with these two disorders. Participants ( n = 61; BD = 19; SZ = 19; healthy controls [HCs] = 23) were administered a semantic judgment task and event‐related potentials (ERPs) were recorded. Responses of the two patient groups were significantly slower than HCs, but comparable behavioral semantic priming effects were observed in both patient groups. The N400 priming effect was observed in all groups, with a delayed peak in the two patient groups. The N400 effect was enhanced for both BD and SZ patients over the left frontal and frontal pole region, but SZ patients showed additional reduction of N400 over the right posterior and occipital regions. The N400 mean amplitudes for related targets correlated with less severe negative symptoms in patients with SZ. Discriminant functional analysis using reaction time and N400 measures successfully classified 82% of the participants into their respective clinical groups. These results suggest that patients with BD and SZ have both overlapping and distinctive semantic processing dysfunction. These findings are consistent with the continuum conceptualization of these disorders, but also offer some support for the traditional Kraepelinian dichotomy.